2016
DOI: 10.1148/radiol.2015142941
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Body Size Index with Which to Determine Iodine Dose for Hepatic Dynamic CT: A Prospective Multicenter Study

Abstract: Among body size parameters, LBW exhibited the strongest correlation with aortic and hepatic enhancement, especially in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 40 publications
2
61
1
Order By: Relevance
“…According to Bae ( 10 ), the blood volume and CO directly affect the enhancement of vessels, by contrast media while other patient characteristics have an indirect effect and manifest a complex relationship. Others ( 18 19 ) have suggested that enhancement is increased in elderly patients. However, most earlier studies did not perform multivariate regression analysis or did not include the CO as an independent factor in their multivariate linear regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…According to Bae ( 10 ), the blood volume and CO directly affect the enhancement of vessels, by contrast media while other patient characteristics have an indirect effect and manifest a complex relationship. Others ( 18 19 ) have suggested that enhancement is increased in elderly patients. However, most earlier studies did not perform multivariate regression analysis or did not include the CO as an independent factor in their multivariate linear regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 , 23 25 ] Consequently, various body size indices such as the LBW and the BSA have been introduced to determine the optimal contrast agent dose for cardiac CT- and hepatic dynamic CT studies and for CTA. [ 26 29 ] Awai et al [ 28 ] suggested that the LBW exhibited the strongest correlation with aortic and hepatic enhancement and Yanaga et al [ 29 ] reported that an LBW-tailored dose yielded more consistent aortic enhancement with reduced interpatient variability than the CTA protocol that delivered a BW-tailored dose. According to Bae et al, [ 26 ] a contrast dose based on the BSA was useful for obtaining consistent contrast enhancement on cardiac CT angiographs.…”
Section: Discussionmentioning
confidence: 99%
“…As in earlier studies, factors with an effect on contrast enhancement, i.e., the patient's age, sex, TBW, and height, were recorded ( 17 18 ). We acquired their age and sex from their electronic health records.…”
Section: Methodsmentioning
confidence: 99%